GREEN MARKETING AND SUSTAINABLE DEVELOPMENT – EXPERIENCES FROM REPUBLIC OF SERBIA - Branislav, Radnovic; Ilic, Milena; D. Zivkovic, Zoran (Journal of Economic Development, Environment and People, 2012)
The world must be developed according to the needs of people, but with the obligation of sustainable development as a comprehensive process that depress all aspects of life, at all levels. Sustainable development is about making models in a qualitative way to meet the socio-economic needs and interests of citizens, while eliminating or significantly reducing the impacts that threaten or harm the environment and natural resources. Sustainable development of mankind leads to a sustainable society in which man has good control of the planet and responsible custodian of heritage for future generations. Sustainable development is without a doubt, as a result of the coming dramatic changes requested in all areas of life of every individual. Changes are related to the change in our spending habits (which in itself is already hard enough) and the change of consciousness in the fields of economics, politics and society. Companies that are self-conscious to environment with potential for business and profits, also realize a significant contribution to environmental protection. These successful companies not only sell products to its customers and thus gain profits, but in the corporate commitment to make decisions for the care of their surroundings. In contrast to conventional producers, the most successful green companies direct their customers, or in advance know what needs to be made and the buyer offers an environmentally friendly product. Green companies are ready to address concerns about the natural environment. Green marketing is the primary segment of social marketing, because it covers the protection and preservation of the values necessary for survival, existence and development of man as a human being, reflecting the practical support the implementation of the philosophy of sustainable development of mankind. Green marketing presents important opportunities for industry and economy of the Republic of Serbia. Therefore Serbian companies must re-define the roles of business and products, as well as joint work with government agencies, consumer groups and NGOs. Serbia is becoming aware of environmental issues, but for green marketing businesses, companies, consumers and government still do not pay enough importance.